2006
DOI: 10.1038/sj.cgt.7700982
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with liposome–DNA complexes elicits enhanced antitumor immunity

Abstract: Cationic liposomes have been shown to potentiate markedly the ability of plasmid DNA to activate innate immune responses. We reasoned therefore that liposome-DNA complexes (LDC) could be used to produce more effective plasmid DNA vaccines for cancer. To test this hypothesis, tumor-bearing mice were vaccinated with conventional plasmid DNA vaccines or with LDC vaccines encoding model tumor antigens and CD8 þ T-cell responses and antitumor activity were assessed. We found that although plasmid DNA vaccines gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Previous studies have indicated that NK cells were the major source of IFN-␥ production following systemic (i.v.) treatment with CLDC (10,34). However, the role of NK cells in mediating CLDC-induced pulmonary immunity to bacterial challenge has not been explored previously.…”
Section: Ifn-␥ Is Necessary For Cldc-mediated Protection In Vivomentioning
confidence: 99%
“…Previous studies have indicated that NK cells were the major source of IFN-␥ production following systemic (i.v.) treatment with CLDC (10,34). However, the role of NK cells in mediating CLDC-induced pulmonary immunity to bacterial challenge has not been explored previously.…”
Section: Ifn-␥ Is Necessary For Cldc-mediated Protection In Vivomentioning
confidence: 99%
“…Among synthesized cholesterol derivatives, there is a commercially available lipid, 3-b-[N-(N 0 ,N 0 -dimethylaminoethyl)carbamoyl]-cholesterol (DC-Chol). Liposomes prepared with DC-Chol and DOPE lipids are widely used to deliver the plasmid DNA for tumor immunotherapy 19,20 or artificial immunization 21 and are under clinical trials for the therapy of mucoviscidosis. 22 As mentioned above, lipids with different positively charged groups based on aliphatic or heterocyclic bases were synthesized to reveal the structure-activity relationships between the structure of cationic lipids and the transfection activities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, liposome-DNA vaccine complex was more effective at increasing CD8+ T cell numbers and controlling established tumors through the production of IL-12 from dendritic cells and of IFN- from NK cells, as compared with DNA vaccines alone. 71 Similarly, higher anti-melanoma immune responses were elicited by formulation of DNA vaccines with nanoparticle, as compared with DNA vaccines alone. 72 Thus, the use of these formulations and newer delivery strategies likely hold promise for augmenting the potency of cancer DNA vaccines.…”
Section: Use Of Different Dna Delivery Methodsmentioning
confidence: 98%